The Effect of Digital Flashcard Media on Vocabulary Improvement of Elementary School Students - Musiman, Musiman; Fitriana, Meida (EXPOSE (Journal of English Education and for Specific Purpose), 2025)
Vocabulary mastery is a fundamental component of language learning that supports students’ abilities in reading, writing, speaking, and listening. However, many elementary school students still experience difficulties in understanding and using vocabulary effectively due to limited instructional media and teacher-centered learning approaches. This study aims to investigate the effect of digital flashcard media on vocabulary mastery among elementary school students at SD Negeri 2 Sukoharjo, Pringsewu, Lampung. The study employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The participants consisted of 30 fourth-grade students selected through total sampling. Data were collected using a vocabulary test comprising 20 objective items administered before and after the implementation of digital flashcard-based instruction. The collected data were analyzed using descriptive statistics and inferential analysis in the form of a paired sample t-test. The results showed a significant improvement in students’ vocabulary mastery after the use of digital flashcards. The mean score increased from 60.13 in the pretest to 82.47 in the posttest. Indicator-based analysis revealed improvements in word meaning recognition, word–image matching, vocabulary usage in sentences, and vocabulary recall. The paired sample t-test indicated a significant difference between pretest and posttest scores at the 0.05 significance level (p < 0.05), confirming the effectiveness of digital flashcard media. The findings suggest that digital flashcards are an effective instructional medium for enhancing vocabulary learning at the elementary school level. Visualized vocabulary presentation and repeated exposure through digital flashcards support students’ comprehension and retention. This study provides empirical evidence supporting the integration of digital learning media in elementary language instruction and offers practical implications for teachers seeking innovative strategies to improve vocabulary mastery.